The emergence of monumental architecture in Atlantic Europe: a fortified fifth-millennium BC enclosure in western France. (February 2023) - Ard, Vincent; Onfray, Marylise; Aoustin, David; Bouchet, Éric; Bruniaux, Guillaume; Dandurand, Grégory; Daniel, François; Dufraisse, Alexa; Granai, Salomé; Laurent, Antoine; Legrand, Victor; Lévêque, François; et al.
Abstract: Abstract: The earliest monumentality in Western Europe is associated with megalithic structures, but where did the builders of these monuments live? Here, the authors focus on west-central France, one of the earliest centres of megalithic building in Atlantic Europe, commencing in the mid fifth millennium BC. They report on an enclosure at Le Peu (Charente), dated to the Middle Neolithic ( c . 4400 BC), and defined by a ditch with two 'crab claw' entrances and a double timber palisade flanked by two timber structures—possibly defensive bastions. Inside, timber buildings—currently the earliest known in the region—were possibly home to the builders of the nearby Tusson long mounds.